Optimization Of Bil Wakalah Murabahah Contracts Towards The Responsibility Of Sharia Banking Kur Finance - Pratama, Muhamad Zundi; Noviarita, Heni Noviarita; Sanjaya, Frenky Sanjaya (Universitas Islam Negeri Raden Intan Lampung, 2023)
One of the banks that collects funds from the public and distributes it back to customers in the form of financing is Islamic Banks, one of the financing products channeled is People's Business Credit (KUR) financing. In implementing KUR financing, Islamic banks use a murabahah bil wakalah contract. Optimization of murabahah bil wakalah contracts will be discussed for the responsibility of Islamic banking credit financing using data analysis methods. People's Business Credit (KUR) which aims to support Indonesian Micro and Small Enterprises (UMK) licensing. Bank Indonesia's KUR, stated that in the implementation of credit there were several obstacles in the business of a community concept, this KUR was fully guaranteed by the government. The contract in KUR is a Murobahah contract, namely buying and selling where the investor provides the goods the customer wants, then the financier provides the goods the customer wants at a purchase price plus a certain profit price. order, Murabaha determines a certain rate of return can buy or not Murabaha is a contract to buy and profit is agreed between the seller and the buyer. The most important thing that distinguishes traditional banks from Islamic banks is the determination of the selling price and purchase price. Conventional banks always base their pricing on interest rates, while Islamic banks are based on Islamic concepts. The Islamic concept is cooperation in a profit-sharing system in times of wins and losses. Everything related to sharia banks and sharia business entities. This is the form of a Murabahah contract where Murabahah can be made on behalf of the Bank for the goods later. Orders received from subscribing customers. According to the type of product in Islamic banking, namely financing of products offered by Islamic banking, including mandatory savings, savings and investments. Akad used for Mudharabah financing. Financing, namely financing for products offered by Islamic Banking for commercial purposes. The contracts for financing products are Murabahah, Musyarokah and IMBT. Services, namely products offered by Islamic banks to meet business and personal needs, such as product services, operational services and investment services. including mandatory savings, savings and investments. Akad used for Mudharabah financing. Financing, namely financing for products offered by Islamic Banking for commercial purposes. The contracts for financing products are Murabahah, Musyarokah and IMBT. Services, namely products offered by Islamic banks to meet business and personal needs, such as product services, operational services and investment services. including mandatory savings, savings and investments. Akad used for Mudharabah financing. Financing, namely financing for products offered by Islamic Banking for commercial purposes. The contracts for financing products are Murabahah, Musyarokah and IMBT. Services, namely products offered by Islamic banks to meet business and personal needs, such as product services, operational services and investment services.